"Wealth from metal waste": Translating global knowledge on industrial ecology to metals recycling in Australia. (15th May 2015) - Corder, G.D.; Golev, A.; Giurco, D.
Highlights: Waste materials are now becoming accessible and valuable as 'above-ground' mineral resources. Australia must anticipate and adapt to the implications of a rise in the importance of recycling. The value of metals in end-of-life products in Australia is estimated at over AUD6 billion per year. The potential for recovering metals from end-of-life products is about AUD2 billion per year. About 2.5 million tonnes per year of scrap metal collected in Australia is transported overseas. Abstract: Australia's rich stocks of mineral resources have been the source of national wealth and competitive advantage in the past. However, the security of this wealth is not guaranteed into the future, and what were once considered waste materials from mining, infrastructure and products are now becoming accessible and valuable as 'above-ground' mineral resources. Globally there is growing capacity and innovation in recycling, closed-loop supply chains and Australia's role as a global leader in primary production must anticipate and adapt to the implications of a rise in the importance of recycling. However, both at a global level and in Australia, there are a broad range of factors and local influences affecting the successful application and implementation of industrial ecology beyond technical re-use solutions. This paper presents the initial outcomes from a major collaborative research project (Wealth from Waste Cluster), funded by the CSIRO Flagship Collaboration Fund and partner universities, focused on identifying viable options to 'mine' metals contained in discarded urban infrastructure, manufactured products and consumer goods. This paper presents initial estimates of the mass and current worth of metals in end-of-life products. Results from this analysis have identified that the value of metals in end-of-life products is more than AUD6 billion per year, and assuming existing recovery rates, the estimated potential for recovering metals from "waste" or end-of-life products is of the order of AUD2 billion per year. In addition a metal flow analysis of the Australian economy identified that approximately half the scrap metal collected in Australia (approximately 2.5 million tonnes per year) is currently being transported overseas which potentially could be recycled in Australia if suitable technology were available.